A comparison of the parameters of the chromatographic separation of the mixture of dyes obtained by caLC on the adsorbents type RP-8 and RP-18. Issue 7 (September 2017) - Gierak, Andrzej; Skorupa, Agata
The aim of the presented research was to compare the chromatographic separation process, a mixture of food dyes obtained in capillary action liquid chromatography (caLC) columns packed with adsorbent type RP-8 and RP-18 and using as the eluent: methanol-water-acetic acid (4:5:1, v/v). The obtained retention data were compared with separation in caLC columns with different internal diameters, different distance of migration and the different mode of development the chromatograms.